2019
DOI: 10.21608/eajbsf.2019.29347
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Gamma Irradiation in Controlling the Red Flour Beetles, Tribolium castaneum Herbst, and Preventing Its Secondary Infestations

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Sileen et al observed in T. castaneum that the dose of 1 kGy provides total mortality of individuals from the seventh day after treatment in wheat flour, in addition, they found that radiation eliminates fungi and bacteria from the surface of the food and inhibits the effect of quinones, secreted by the insect, which can cause cancerous changes in human and animal tissue cells after consumption [34].…”
Section: Resultsmentioning
confidence: 99%
“…Sileen et al observed in T. castaneum that the dose of 1 kGy provides total mortality of individuals from the seventh day after treatment in wheat flour, in addition, they found that radiation eliminates fungi and bacteria from the surface of the food and inhibits the effect of quinones, secreted by the insect, which can cause cancerous changes in human and animal tissue cells after consumption [34].…”
Section: Resultsmentioning
confidence: 99%